Innovation “KARSU PELUK SI IBU” (Card for Husband cares for Mother’s High-Risk Health Efforts) Sempor 1 Health center, Kebumen Regency - Eka Riyanti; Herniyatun (BEMAS: Jurnal Bermasyarakat, 2022)
Maternal and neonatal mortality rates are indicators used to determine public health status. Health services that have been carried out to reduce maternal mortality by the Sempor 1 Health Center were visited by pregnant women and neonates, assistance efforts by health workers, postpartum maternal services, pregnant women receiving iron tablets and TT techniques, handling of obstetric and neonatal complications, family planning services, and health services. nutrition. However, the services that have been done, there was no service that included husbands and families of the pregnant women who live in the same house. The purpose of this service was to carry out the KARSU PULUK SI IBU program for high-risk pregnant women. This community service method was lecture, discussion and mentoring. The community service participants were 5 midwives of the Health Center, 13 village midwives, and 10 pairs of high-risk pregnant women. The result of this activity was an agreement to implement the KARSU PELUK SI IBU program at the Sempor 1 Health Center. Knowledge improvement in 10 couples who were given education and mentoring during the program was proven by the average pretest score of 65 and the post-test average of 77 (increasing by 12). Conclusion the KARSU PELUK SI IBU program was carried out on 10 pairs of high-risk pregnant women, high-risk pregnant women were monitored and received support from their husbands